PENGEMBANGAN PUSAT BUDAYA PETALANGAN SEBAGAI OBJEK WISATA BUDAYA DI KECAMATAN PANGKALAN KURAS KABUPATEN PELALAWAN - Meri Gustiani; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Petalangan Cultural Center is one of the cultural tourism objects in Pelalawan Regency. In spite of its good potential, the Petalangan Cultural Center is not managed properly to such extent that it is being neglected which has an impact on decreasing the number of visits to the Petalangan Cultural Center. This research aims to describe the Petalangan Cultural Center as a cultural tourism object. This research uses a qualitative method with a descriptive approach. The key informants in this study were the head of the tourism object development section of the Tourism, Youth and Sports Office of Pelalawan Regency, the manager of the Petalangan Cultural Center tourist attraction, the Petalangan Malay ethnic leaders, the community around the Petalangan Cultural Center, and visitors to the Petalangan Cultural Center. Data collection techniques used in this research were observation, documentation, and interviews. Based on the results of the research, it can be seen that the condition of the Petalangan Cultural Center as a cultural tourism object has been truly neglected at which point that it makes various unique ethnical activities of the Petalangan Malay tribe abolished for it is one of the attractions of cultural tourism at the Petalangan Cultural Center. To boot, the historical buildings and other general facilities at the Petalangan Cultural Center were not managed properly so much as being damaged to various extents.Keywords: Tourism Objects, Cultural Tourism, Petalangan Cultural Center.